Orientation of IS50 transposase gene and IS50 transposition. - Makris, J C (1989)
Reversal of transposase gene orientation with respect to the nonidentical ends of IS50 strongly decreased IS50 transposition in both Dam- and Dam+ hosts. In either orientation, IS50 transposase expression was unaffected. These effects were independent of the surrounding DNA context. This shows that the efficiency of IS50 transposition is dependent on transposase gene orientation. The transposition frequencies of transposons utilizing inverted IS50 inside ends (IE), IE-IE transposons, were lower than either outside end (OE)-IE or OE-OE transposons.